Transanal opening of the intersphincteric space: a novel sphincter‐sparing procedure to treat 325 high complex anal fistulas with long‐term follow‐up. (19th February 2021) - Garg, Pankaj; Kaur, Baljit; Menon, Geetha R.
Abstract: Aim: Sepsis in the intersphincteric plane behaves like an abscess in a closed space and is present in most complex fistulas. Ignoring this sepsis is a cause of recurrence. Complex fistulas can be successfully managed by transanal opening of the intersphincteric space (TROPIS) into the anal canal. The long‐term efficacy of the TROPIS procedure was analysed in an exclusive cohort of high complex anal fistulas. Methods: All consecutive patients operated for a high complex fistula‐in‐ano were included prospectively. Preoperative MRI scans were obtained for all the patients. The intersphincteric space and internal opening was laid open into the anal canal while preserving the external sphincter. The external tracts were thoroughly curetted and cleaned. Fistula healing rate and objective incontinence scores (preoperatively and during long‐term follow‐up) were analysed. Results: A total of 325 patients (age 39.9 ± 10.9 years, 292 men) were operated with TROPIS and had a follow‐up of 7–67 months (median 36 months). In the cohort, 67.4% (219) had recurrent fistulas, 82.8% (269) had multiple tracts, 36.3% (118) had horseshoe tracts, 37.5% (122) had associated abscesses and 24% (78) were supralevator fistulas. Nineteen patients were excluded. Fistulas healed completely in 78.4% (240/306) of patients and did not heal in 21.6% (66/306) of patients. 36/66 of these patients were operated again and the fistulas healed in 28 patients. Thus, the overall healing rate was 87.6% (268/306). The mean preoperative and postoperative incontinence scores were 0.085 ± 0.35 and 0.119 ± 0.48 respectively ( P  = 0.38). The healing rate of fistulas with associated acute abscesses was similar to the fistulas without abscesses (87% vs. 88%, P  = 0.85). Conclusion: Transanal opening of the intersphincteric space is a safe and highly effective sphincter‐sparing procedure to manage high complex fistulas‐in‐ano.